Analisis Sastra Murni (Unsur Intrinsik) dan Sastra Terapan (Psikologi-Sosiologi) dari Novel Quiet Goodbye Karya Nisfatul Amaliya - Amaliya, Nisfatul (EUNOIA (Jurnal Pendidikan Bahasa Indonesia), 2025)
Abstrak:This research entitled “An Analysis of Nisfatul Amaliya’s Novel Quiet Goodbye Based on Intrinsic Elements, Psychological Approach, and Sociological Approach” aims to: (1) describe the intrinsic elements of the novel Quiet Goodbye, (2) analyze the psychological dynamics of the characters through a psychological approach, and (3) examine the social and cultural values reflected in the novel using a sociological approach.This study is a qualitative research using a descriptive-analytical method. The primary data source is Nisfatul Amaliya’s novel Quiet Goodbye, while the secondary data sources consist of literary theories, journals, and other relevant references. The data were collected through careful reading, note-taking, and categorizing relevant quotations. The data were analyzed by applying intrinsic analysis, psychological approach, and sociological approach.The findings show that the intrinsic elements of Quiet Goodbye include: (a) the theme of educational struggle, love, and religiosity, (b) the main character, Addara Yasmine (Dara), who is portrayed as intelligent and religious, supported by other characters such as Mandy, Hilman, and Della, (c) a progressive plot with flashbacks, (d) the setting of Yogyakarta and Lombok, (e) conflicts between ambition and love, and (f) moral messages emphasizing the importance of faith, education, and family.From the perspective of psychological criticism, the main character Dara experiences inner conflict between love and ambition, as well as longing for her family. Mandy is portrayed as a mature figure with strong self-control and religiosity in dealing with his feelings. From the sociological perspective, the novel reflects the social reality of students living far from home, the role of religiosity in daily life, and the medical profession as a form of social dedication.In conclusion, Quiet Goodbye is not only an entertaining literary work but also conveys profound messages about education, love, faith, and the social realities of Indonesian society.Keywords: Quiet Goodbye, intrinsic analysis, psychological approach, sociological approach.